Shipment of pre-fabricated steel building (Shipment of steel structure against LC no. 0000021619010057 dated: 26.02.19) - Brac University (Brac University, 2023)
This record consists of general correspondence regarding shipment of pre-fabricated steel building (Shipment of steel structure against LC no. 0000021619010057 dated: 26.02.19) of BRAC University new campus project.